Implementation of the Merdeka Curriculum in Islamic Religious Education as an Effort to Strengthen Students’ Religious Character at State Junior High School 1 Bendosari - Sri Haryati; Muhammad Isa Anshory (At Turots: Jurnal Pendidikan Islam, 2026)
This study aims to describe the implementation of the Merdeka Curriculum in Islamic Religious Education (PAI) as an effort to strengthen students’ religious character at SMP Negeri 1 Bendosari, and to analyze its supporting and inhibiting factors. This research employed a qualitative descriptive method with a field research approach. Data were collected through observation, interviews, and documentation involving the principal, Islamic Education teachers, and students. The results revealed that the Merdeka Curriculum has been implemented through intraclass, co-curricular, and religious habituation activities such as Qur’an memorization (tahfidz), congregational prayers, daily supplications, and the smile, greeting, and respect program. The key supporting factors include school policy support, teacher exemplarity, a strong religious culture, and parental involvement. In contrast, the main obstacles are limited time, insufficient worship facilities, and diverse religious backgrounds among students. The findings imply that Islamic Religious Education within the Merdeka Curriculum framework effectively fosters students’ moral and spiritual character, reinforcing the Pancasila Student Profile of faith and noble character.